ADVANTAGES AND DISADVANTAGES OF TEACHING ENGLISH TO PRESCHOOL CHILDREN - Tojimurodova Khurshida Rashidovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study examines the advantages and disadvantages of teaching English to preschool-aged children, focusing on the cognitive, linguistic, and social outcomes associated with early language learning. Using a combination of literature review, observational case studies, and experimental data, the research highlights key benefits such as enhanced cognitive development, improved linguistic skills, and increased cultural awareness. However, challenges including cognitive overload, resource constraints, and potential impacts on cultural identity are also identified. The findings emphasize that while early English education offers significant benefits, its success depends on structured implementation and cultural sensitivity. This paper provides actionable insights for educators and policymakers to optimize early language learning practices.